Pedagogical culture of parents: challenges and ways of formation - Voronova Svitlana (Науковий Вісник Південноукраїнського Національного Педагогічного Університету імені К. Д. Ушинського, 2020)
The article considers the formation of parents’ pedagogical culture as an important factor in the development of general secondary education which ensures the quality of educational services. The analysis of the scientific and pedagogical literature, researches of the UNICEF and the National Children’s Hotline shows that the issue of forming parents’ pedagogical culture gains ground. According to the theory of generations, participants of the educational process belong to different age groups and there is a need to clarify the issue concerning how to establish their joint interaction to ensure the quality of education. Under such conditions, child’s parents must be pedagogically literate, be able to organise and implement effective family education, joint activities together with an educational institution to create an atmosphere of trust and mutual respect, where there is no violence or discrimination. The educational resource for parents is directly dependent on the level of their pedagogical culture formation as one of the components of their family life. Under parents’ pedagogical culture, we understand a system of pedagogical knowledge, pedagogical and psychological competence, which are aimed at the upbringing and development of a child. Moral, communicative, didactic, physical, aesthetic components; environmental culture and culture of thinking; speech, work, and moves are the components of parents’ pedagogical culture which are to be considered. The formation of parents’ pedagogical culture can be carried out by motivational, semantic and constructive components and is aimed at parents’ awareness of the need for pedagogical knowledge, their readiness to be an active participant in the education and upbringing process of the child. In the process of forming parents’ pedagogical culture, the teacher must constantly improve the skills of positive pedagogical communication, the validity of parents’ pedagogical position; introduce active forms of their learning; use the principles of partnership pedagogy and teamwork.